Accounting technologies and reporting in cost management of transfer pricing operations on the basis of sustainable development - Paranytsia, Nadiia Volodymyrivna (Поліський національний університет, 2024)
The monograph chapter examines current trends in the development of large domestic enterprises in the context of increasing complexity of business operations and organizational diversification. It analyzes management challenges arising from the territorial dispersion and multi-industry structure of modern business entities, which hinder effective decision-making under centralized management systems. The study substantiates decentralization of management as a natural stage in the evolution of large enterprises, involving the delegation of part of managerial functions to the middle management level. The role of subsidiary companies is highlighted as a mechanism for combining the advantages of centralized management (synergy effects) with those of decentralized structures (flexibility and rapid adaptation to changing external conditions). It is emphasized that a balanced integration of these approaches is a key prerequisite for improving the efficiency of modern corporate governance.

У розділі монографії досліджено сучасні тенденції розвитку великих вітчизняних підприємств у контексті ускладнення масштабів господарювання та зростання організаційної багатогалузевості. Проаналізовано проблеми управління складними бізнес-структурами, зумовлені їх територіальною роз’єднаністю та розширенням сфер діяльності, що ускладнює ефективне прийняття управлінських рішень в умовах централізованої системи. Обґрунтовано необхідність децентралізації управління як закономірного етапу розвитку великих підприємств, що передбачає передачу частини управлінських функцій на середній рівень менеджменту. Визначено роль створення дочірніх компаній як інструменту поєднання переваг централізації (ефект синергії) та децентралізації (гнучкість і швидка адаптація до змін зовнішнього середовища). Наголошено, що збалансоване поєднання цих підходів є ключовою умовою підвищення ефективності управління сучасними корпоративними структурами.
Keywords: accounting technologies; reporting; cost management; transfer pricing operations; sustainable development; облікові технології; звітність; управління витратами; операції трансфертного ціноутворення; сталий розвиток